Syntesis and Characterization of Complexes Anthranilic Acid With Some Metal Ions - Al-Noor, I.H.; Al-Dohan, I. A.; Abd-AI-Magide, I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The  research includes attempts to prepare anthranil ic acid (C7H7N02) complexes  with some metals: [Pd (II), Fe(ll), and  Fe (Ill))  which have been characterized by using:Thermal stability (melti ng point, d composition poit), molar conductivity, IR,   UV-visible   spectra,   elemental   analysis   (C-H-N)   and   magnetic properties.  The   general  formula   has   been  given for  the   prepared complexes:-- M(C2H6N02)2 Where M= [Pd(ll), Fe(TI), Hg(ll)] :.. M(C1H6N02)l Where  M= [Fe(llf)]